Variability of rock erodibility in bedrock‐floored stream channels based on abrasion mill experiments. Issue 8 (4th August 2015) - Small, Eric E.; Blom, Tevis; Hancock, Gregory S.; Hynek, Brian M.; Wobus, Cameron W.
Abstract: We quantify variations in rock erodibility, Kr, within channel cross sections using laboratory abrasion mill experiments on bedrock surfaces extracted from streams with sandstone bedrock in Utah and basaltic bedrock in the Hawaiian Islands. Samples were taken from the thalweg and channel margins, the latter at a height that is inundated annually. For each sample, a sequence of abrasion mill experiments was completed to quantify variations in erosion rate with erosion depth. Erosion rate data from these experiments shows two things. First, the erosion rate from channel margin samples is greater than for thalweg samples, with the greatest difference observed for the rock surface that was exposed in the stream channel. Second, erosion rate decreases with depth beneath the original rock surface, by an order of magnitude in most cases. The erosion rate becomes steady at depths of 1–3 mm for channel margin samples and 0.1–0.4 mm for thalweg samples. Because only rock properties and microtopography vary throughout the sequence of mill experiments, these results suggest that Kr of the bedrock surface exposed in stream channels is higher at the margins than near the channel center and that Kr decreases over depths of 1 mm. The simplest explanation for these patterns is that Kr is enhanced, at the bedrock surface and along the channel margins, due to the effects of weathering on rock strength and surface roughness. We hypothesize that a balance exists between weathering‐enhanced erodibility and episodic incision to allow channel margins to lower at rates similar to the thalweg. Key Points: A laboratory abrasion mill was used to quantify variations in rock erodibility Rock erodibility varies with erosion depth and position in stream channels Variations in erodibility are consistent with the expected effects of weathering